Bioimmunological activities of Candida glabrata cellular mannan. Issue 2 (28th January 2019) - Paulovičová, Lucia; Paulovičová, Ema; Farkaš, Pavol; Čížová, Alžbeta; Bystrický, Peter; Jančinová, Viera; Turánek, Jaroslav; Pericolini, Eva; Gabrielli, Elena; Vecchiarelli, Anna; Hrubiško, Martin
ABSTRACT: Candida glabrata is a second most common human opportunistic pathogen which causes superficial but also life-threatening systemic candidosis. According to the localisation of mannans and mannoproteins in the outermost layer of the cell wall, mannan detection could be one of the first steps in the cell recognition of Candida cells by the host innate immune system. Mannans from the cell wall provide important immunomodulatory activities, comprising stimulation of cytokine production, induction of dendritic cells (DCs) maturation and T-cell immunity. The model of DCs represents a promising tool to study immunomodulatory interventions throughout the vaccine development. Activated DCs induce, activate and polarise T-cell responses by expression of distinct maturation markers and cytokines regulating the adaptive immune responses. In addition, they are uniquely adept at decoding the fungus-associated information and translate it in qualitatively different T helper responses. We find out, that C. glabrata mannan is able to induce proliferation of splenocytes and to increase the production of TNF-α and IL-4. Next, increased the expression of co-stimulatory molecules CD80 and CD86 and the proportion of CD4 + CD25 + and CD4 + CD28 + T cells during in vitro stimulation of splenocytes. Reported results provide C. glabrata mannan capability to modulate cytokine production, DCs activation and antigen presentation activity, influencing T-cell phenotype in response to stimulation. Abstract : Reported results provide C. glabrata mannan capability to modulate cytokine production, DCs activation and antigen presentation activity, influencing T-cell phenotype in response to stimulation.